Who Buys Counterfeit Luxury Brands? A Meta-Analytic Synthesis of Consumers in Developing and Developed Markets. Issue 4 (December 2017) - Eisend, Martin; Hartmann, Patrick; Apaolaza, Vanessa
Although numerous previous studies have investigated consumer demographics and psychographics as determinants of counterfeit purchases, their findings are diverse and fragmented. In conceptually referring to the brand signals that help consumers build their identities, the present meta-analysis synthesizes the influence of consumer demographics and psychographics on attitudes, intentions, and behaviors with regard to branded counterfeit luxury products. It empirically summarizes 610 effect sizes from 98 independent studies and shows that whereas demographics have little impact, some psychographics greatly influence counterfeit purchases, with these influences differing between developed and developing countries. In the former, risk propensity and reduced integrity are stronger determinants of counterfeit purchases and are related to brand signals that refer to identities that consumers attempt to avoid. In developing countries, consumers are more influenced by psychographics, such as status seeking, which are related to positive brand signals for consumer identities. The findings lead to a profile of consumers of counterfeit luxury items that provides guidance for future research and for improved consumer targeting with regard to international anticounterfeiting measures.